Nursing of an elderly patient with chronic constipation treated by auricular acupoint sticking and pressing therapy (耳穴贴压治疗老年慢性便秘1例的护理体会) - YE Yun (叶云); CAO Fang (曹芳); TIAN Zheng (田征) (Association of Integrative Nursing, 2022)
To summarize the nursing experience of an elderly patient with chronic constipation of Qi-blood deficiency syndrome treated by auricular acupoint sticking and pressing therapy. On the basis of routine nursing such as dietary nursing, psychological adjustment and health education, the auricular acupoint sticking therapy was performed. According to the characteristics of disease and the patient, targeted nursing measures were carried out to relieve the constipation and related clinical symptoms. (总结耳穴贴压治疗1例老年慢性气血两虚型便秘患者的护理经验。在完善饮食护理、心理调适、健康指导等常规护理的基础上, 给予耳穴贴压治疗, 并根据疾病和患者特点, 采用相应的护理措施, 积极改善患者便秘症状。)